2018
DOI: 10.1038/s41598-018-22159-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient detection of Zika virus RNA in patients’ blood from the 2016 outbreak in Campinas, Brazil

Abstract: Infection with Zika virus (ZIKV), a mosquito-borne flavivirus has been casually linked with increased congenital microcephaly in Brazil from 2015 through 2016. Sensitive and specific diagnosis of patients with Zika fever (ZIKF) remains critical for patient management. We developed a ZIKV NS5 qRT-PCR assay by combining primers described by Balm et al. and a new Taqman probe. The assay was evaluated and compared with another assay described by Lanciotti et al. (ZIKV 1107) using 51 blood and 42 urine samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In NHP models, ZIKV-associated birth defects (especially neuropathology) appear to be severe and extremely common [8,68], which may not perfectly recapitulate human infection in which the prevalence of CZS is thought to be approximately 5% [69]. While ZIKV genomic RNA copy numbers in PBMC samples in the sheep study were low, this is consistent with the low-level viremia well-documented among human ZIKV patients [54,70,71,72]. Although RT-PCR does not allow for determination of replicating virus, ZIKV RNA copy number per mL detected in PBMC samples from one infected ewe fluctuated dramatically between D1 and D7 PI, implicating viral replication (Figure 3b).…”
Section: Discussionmentioning
confidence: 63%
“…In NHP models, ZIKV-associated birth defects (especially neuropathology) appear to be severe and extremely common [8,68], which may not perfectly recapitulate human infection in which the prevalence of CZS is thought to be approximately 5% [69]. While ZIKV genomic RNA copy numbers in PBMC samples in the sheep study were low, this is consistent with the low-level viremia well-documented among human ZIKV patients [54,70,71,72]. Although RT-PCR does not allow for determination of replicating virus, ZIKV RNA copy number per mL detected in PBMC samples from one infected ewe fluctuated dramatically between D1 and D7 PI, implicating viral replication (Figure 3b).…”
Section: Discussionmentioning
confidence: 63%
“…Urine and saliva are useful clinical samples for ZIKV detection, given that ZIKV can be found at higher levels in both saliva and urine as compared to serum [26,27]. However, viral RNA levels are still quite low, with urine samples from the 2016 ZIKV outbreak in Brazil containing 3.66-3568.61 copies [28]. CHIKV can also be found in saliva and urine [29,30], but use of these samples did not enhance the detection rate [29].…”
Section: Discussionmentioning
confidence: 99%
“…All cases notified to the Malaysian ZIKV clinical surveillance system had both blood and urine samples tested with rRT-PCR for confirmation of ZIKV infection. Although the duration of detectable ZIKV RNA in serum is relatively short, studies had shown ZIKV RNA remain detectable in urine for a longer duration after becoming undetectable in the serum [33, 35, 52, 53]. Because patients sought medical attention while they still had symptoms, it is unlikely that screening of both serum and urine samples would miss out on positive cases of ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%